2003
DOI: 10.1037/0735-7044.117.6.1292
|View full text |Cite
|
Sign up to set email alerts
|

Opioid Receptors Regulate the Extinction of Pavlovian Fear Conditioning.

Abstract: Rats received a single pairing of an auditory conditioned stimulus (CS) with a footshock unconditioned stimulus (US). The fear (freezing) that had accrued to the CS was then extinguished. Injection of naloxone prior to this extinction significantly impaired the development of extinction. This impairment was mediated by opioid receptors in the brain and was not observed when naloxone was injected after extinction training. Finally, an injection of naloxone on test failed to reinstate extinguished responding tha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

8
102
0

Year Published

2006
2006
2014
2014

Publication Types

Select...
7
2
1

Relationship

1
9

Authors

Journals

citations
Cited by 89 publications
(110 citation statements)
references
References 38 publications
8
102
0
Order By: Relevance
“…In particular, opioids modulate learning that occurs when there is no shock involved, such as extinction. In fact, earlier work suggested that extinction of active avoidance is impaired by opiate antagonists 213,214 (but see Vigorito and Ayres 215 ) and facilitated by certain opioids 213,214 Consistent with these older findings, McNally and co-workers 216 have found that systemic administration of naloxone before extinction training profoundly retards the development of extinction of freezing to a tone both within and between extinction training sessions. The effect is mediated by central, not peripheral, opioid receptors and is not a consolidation or expression effect because naloxone administration immediately after extinction training or before test has no effect.…”
Section: Neurotransmitter Systemsmentioning
confidence: 69%
“…In particular, opioids modulate learning that occurs when there is no shock involved, such as extinction. In fact, earlier work suggested that extinction of active avoidance is impaired by opiate antagonists 213,214 (but see Vigorito and Ayres 215 ) and facilitated by certain opioids 213,214 Consistent with these older findings, McNally and co-workers 216 have found that systemic administration of naloxone before extinction training profoundly retards the development of extinction of freezing to a tone both within and between extinction training sessions. The effect is mediated by central, not peripheral, opioid receptors and is not a consolidation or expression effect because naloxone administration immediately after extinction training or before test has no effect.…”
Section: Neurotransmitter Systemsmentioning
confidence: 69%
“…Thus, blocking endogenous μ-opioid neurotransmission enhances the acquisition of conditioned fear (43) and impairs the acquisition of extinction or learned safety (44)(45)(46). The implication of these findings is that μ-opioids are involved in reducing conditioned fear responses and enhancing fear extinction or learned safety.…”
Section: Discussionmentioning
confidence: 95%
“…In a Pavlovian fear conditioning paradigm, fear conditioning increases the transcriptional activity of opioidcontaining neurons in the amygdala (Petrovich et al, 2000). Acute administration of opioid antagonists facilitates the acquisition (Fanselow and Bolles, 1979;Young and Fanselow, 1992) and prevents the extinction (McNally and Westbrook, 2003) of fear conditioning.…”
Section: Introductionmentioning
confidence: 99%